Understanding feasibility and patient experiences with a ride share program to facilitate uninsured, Hispanic participation in clinical trials: A pilot survey study. Issue 28 (1st October 2022) - Raygoza, Jhenitza; Rosenblatt, Robert; Austin, Jessica; Omar, Farhia; Cuellar, Idali; Northfelt, Donald W.; Pisano, Etta; Patel, Bhavika K.
Abstract : 91 Background: Most screening clinical trials are not representative of the populations susceptible to disparities in breast cancer outcomes. Strategies are needed to address known structural barriers to clinical trial participation. We partnered with a federally qualified health center to provide no-cost ride-share services as a strategy to facilitate enrollment of uninsured, Hispanic women in Maricopa County, Arizona into a national trial offering no-cost mammography screening. Objective: This pilot survey study explored the feasibility and experiences of uninsured, Hispanic women with a no-cost ride share program as part of the National Cancer Institute funded ECOG-ACRIN clinical trial, TMIST, studying mammography screening at the Mayo Clinic Arizona in Phoenix. Methods: Participants completed a validated survey by phone and interview-style. Survey items assessed women's use of and experiences with the ride share service including barriers, benefits, and if the ride share service facilitated their participation in the screening trial. Descriptive statistics were calculated using SAS. Results: A total of 30 women completed the survey (response rate = 30/33). All women first-time Mayo Clinic trial participants and 90% lived at least 30 minutes away from trial facility. The mean age of women was X years, 90% had a high school degree or less, and 97% were Spanish speaking. Most women (73.7%) said that travel distance was a barrier to participation in prior clinical trials. A large proportion of women (73%) reported using ride share services for this trial and all agreed that the ride service made it easier for them to attend their trial visit. Nearly 1/3 (64%) said that they were uncertain or would not have been able to participate without the ride-share as an option. Among women using the ride share service, the main benefits of the program included at-home pick up and the service being of no-cost. Other benefits included flexible timing (86%) and one-on-one service (86%). The primary barrier of the program was the driver not speaking the dominant native language (27.3%). Conclusions: Despite lengthy travel distances, women reported overwhelming positive experiences with the no-cost ride share program and agreed that the service helped facilitate their participation in the clinical trial. Thus, no-cost ride share programs are a promising and feasible strategy to reduce barriers to clinical trial participation among historically underserved populations. Future studies should continue to explore the benefits and sustainability of ride-share programs, including benefits to clinical trial retention.